Parliamentary procedure handbook : instructor's guide - Yorke, Christopher G. (Longview, WA : Masok Creek Publishing, 2019)
The instructor's guide was written to accompany the Parliamentary Procedure Handbook.
Chapter 1 - Introduction to parliamentary procedure -- Chapter 2. Motions -- Chapter 3. Subsidiary Motions -- Chapter 4. Privileged Motions -- Chapter 5. Incidental Motions. -- Chapter 6. Motions that bring a question again before the assembly.
Keywords: PARLIAMENTARY PRACTICE